2021
DOI: 10.1007/s40618-021-01551-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of moderate exercise on fatty acid oxidation in pancreatic β-cells and skeletal muscle

Abstract: Fatty acids (FA) play a crucial role in glycaemia regulation in healthy and metabolic disorders conditions through various mechanisms. FA oxidation is one of the processes involved in lipid metabolism and can be modulated by exercise. Nowadays, physical activity is known to be an effective strategy for the prevention and treatment of Type 2 Diabetes. Moreover, its intensity, its duration, the sex-gender, the prandial state, exerkines… are as many parameters that can influence glycaemic control. However, the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Lipotoxicity factors: Excess saturated free fatty acids (FFA), diacylglycerol, ceramides, modified carnitine, non-esterified cholesterol, and other hydrophobic molecules can damage mitochondria and other cellular structures [60,[187][188][189]; 4.…”
Section: The Development Of Atherosclerosis Involves Various Factors ...mentioning
confidence: 99%
“…Lipotoxicity factors: Excess saturated free fatty acids (FFA), diacylglycerol, ceramides, modified carnitine, non-esterified cholesterol, and other hydrophobic molecules can damage mitochondria and other cellular structures [60,[187][188][189]; 4.…”
Section: The Development Of Atherosclerosis Involves Various Factors ...mentioning
confidence: 99%
“…In particular, F-HIT exercise led to reductions in fat mass, plasma triglycerides and cholesterol, metabolic syndrome severity, diastolic blood pressure, and concentrations of plasma resistin-a pro-inflammatory adipokine. A recent review has indeed highlighted how only high-intensity physical exercise improves metabolic control at the musculoskeletal level, possible due to the release of myokines, fatty acids, and/or the activation of specific β-cellular receptors for fatty acids [68]. In addition, another study investigating the effects on beta-cell function suggested that F-HIT significantly increased the DI, while no changes in the OGTT-derived first-and second-phase insulin secretion were observed after intervention [43].…”
Section: Exercise Regimens For T2dmmentioning
confidence: 99%
“…Recent research helps to understand this finding, since it has shown that human skeletal muscle cells secrete myokines such as CX3CL1 (fractalkine), which protect β-cells from the negative impact of TNFα [274], and that short-term training improves β-cell function and efficiently reduces ectopic fat within the pancreas in prediabetic or T2D patients [275]. In addition, studies performed on T2D suggest that longduration higher-intensity exercise is less beneficial than moderate-duration and -intensity exercises [276,277].…”
Section: Metabolic Effects Of Lipoxmax Trainingmentioning
confidence: 99%